Unraveling the effect of ambivalence over emotional expression on subjective wellbeing in Chinese college students in romantic relationships: A multiple mediation model - Wang, Yue; Zheng, Zexin; Wang, Xiaoyu; Li, Ying (Frontiers in Psychiatry, 2022)
The sudden and unpredictable outbreak of COVID-19 pandemic have severely threatened young adults' physical and mental health and damaged the quality of relationship. As a critical stage of development, their well-being is more vulnerable to adverse environments which may lead to profound negative long-life mental health status. The current study aimed to investigate the mediation effects of fear of intimacy and attachment avoidance in the association between ambivalence over emotional expression and subjective well-being. A sample of 555 Chinese college students who currently involved in romantic relationships (Mean age =19.69, SD age = 1.36, 52% females) completed anonymous questionnaires regarding ambivalence over emotional expression, fear of intimacy, attachment avoidance, and subjective well-being. The findings revealed that ambivalence over emotional expression can predict negative subjective well-being significantly of college students in romantic relationships, and fear of intimacy and attachment avoidance played a sequentially mediating role in the association between ambivalence over emotional expression and subjective well-being. Surprisingly, when considering attachment avoidance independently, we found it had an inhibitory action on the link between ambivalence over emotional expression. The present study contributes to better understanding how ambivalence over emotional expression can decrease the subjective well-being, and also has implications for the intervention of students' subjective well-being and closeness in the period of COVID-19.